1998
DOI: 10.1002/chin.199841114
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: The Reaction of Phenacyl Malononitrile with Hydrazines: Synthesis of New Pyridazinones and Pyrazolo[1,5‐a]pyrimidines.

Abstract: The Reaction of Phenacyl Malononitrile with Hydrazines: Synthesis of New Pyridazinones and Pyrazolo[1,5-a]pyrimidines. --(ELNAGDI, M. H.; EL-GHAMRY, I.; KANDEEL, E.; RAHMAN, A. H. A.; AL-NAGGAR, A. A.; AMER, S.; RIAD, M.; Gazz.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…When 9 was refluxed in ethanol with hydrazine hydrate a product of molecular formula C 11 H 11 N 5 (213.2) was formed. This proved identical with the product obtained by Abdelrazek [ 12 ] or the one identified by Elnagdi et al [ 13 ]. It thus became clear that 8 had never been isolated and that product believed earlier to be 8 really must have another structure.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…When 9 was refluxed in ethanol with hydrazine hydrate a product of molecular formula C 11 H 11 N 5 (213.2) was formed. This proved identical with the product obtained by Abdelrazek [ 12 ] or the one identified by Elnagdi et al [ 13 ]. It thus became clear that 8 had never been isolated and that product believed earlier to be 8 really must have another structure.…”
Section: Resultssupporting
confidence: 91%
“…It has been previously reported by Abdelrazek et al [ 12 ] that (2-oxo-2-phenylethyl) malononitrile ( 1 ) reacts with hydrazine hydrate to yield 4-phenacylpyrazole-3,5-diamine ( 8 ). Subsequently Elnagdi et al [ 13 ] have shown that the major product of this reaction was in fact the 3-oxo-6-phenyl-2,3,4,5-tetrahydropyridazine-4-carbonitrile ( 9 ). Very recently Abdelrazek [ 14 ] claimed that in ethanolic solution a pyridazineimine was isolated.…”
Section: Resultsmentioning
confidence: 99%